Duality of development and manifestations of PTSD in children with type 1 diabetes during the war in Ukraine - Ivasiuk, Oleksandra; Burlaka , Ievgeniia; Mityuryayeva-Kornijko , Inga (The Ukrainian Scientific Medical Youth Journal, 2025)
in 2019, there were 207,383 registered patients with diabetes in Ukraine, of whom 58,954 had type 1 diabetes.The significance of this issue is directly linked to the strong association between the diagnosis of type 1 diabetes and the development of post-traumatic stress disorder (PTSD), the prevalence of which is rapidly increasing due to the full-scale war in Ukraine. According to recent domestic studies, approximately 25% of Ukraine's population experiences PTSD, and nearly half (57%) are at risk of developing it. The purpose of our study was to examine literature regarding PTSD progression and its impact on children with type 1 diabetes. According to the findings, there are two types of connection between diabetes and PTSD. The first type is based on the physiological response to traumatic stressors, where prolonged exposure of trauma and stress can lead to chronic diseases. The second type of connection indicates that PTSD may develop as a result of an established diagnosis of type 1 diabetes and can by itself directly contribute to PTSD development and progression in patients and their family members. More than 14% of children with type 1 diabetes have associated psychological disorders, such as anxiety, eating disorders, emotional instability, comorbid depression, attention and activity disorders.The practical work of pediatricians and endocrinologists requires a comprehensive, multidisciplinary team approach in treatment of these patients, involving psychologists and psychotherapists.